2001
DOI: 10.1021/bi011262w
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of CMP-Sialic Acid Transport into Golgi Vesicles by Nucleoside Monophosphates

Abstract: We examined the interactions of nucleotides with the CMP-sialic acid transporter in order to better understand which features play a role in binding and to investigate the relationship between binding and subsequent transport. With respect to the sugar, the transporter requires a complete ribose ring for tight binding, and the 2'-ara hydrogen makes an important contact. The enzyme exhibits little specificity with respect to the 2'- and 3'-hydroxyls, as it tolerated substitutions ranging from fluorine to an azi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
20
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(26 citation statements)
references
References 42 publications
2
20
0
Order By: Relevance
“…It should be noted here that intracellular nucleotide sugar concentrations are estimated to be 60 -200 M for UDPGal and 70 -500 M for CMP-Sia (40,41). In view of these values, the K m value of chimera G1 for UDP-Gal may not be too high for the transporter to work with reasonable efficiency in cells.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…It should be noted here that intracellular nucleotide sugar concentrations are estimated to be 60 -200 M for UDPGal and 70 -500 M for CMP-Sia (40,41). In view of these values, the K m value of chimera G1 for UDP-Gal may not be too high for the transporter to work with reasonable efficiency in cells.…”
Section: Discussionmentioning
confidence: 78%
“…hUGT1 and hCST may not strictly discriminate between UMP and CMP, although the affinity of hCST for UMP may not be very high because direct measurement of transport did not detect accumulation of UMP in CST-expressing membrane vesicles. Chiaramonte et al (40) recently examined the substrate specificity of CST in detail and reported that CST can transport UMP, although less efficiently than CMP.…”
Section: Discussionmentioning
confidence: 99%
“…P-3F ax -Neu5Ac presumably enters the intracellular sialic acid synthesis pathway via a salvage pathway and is converted to CMP-P-3F ax -Neu5Ac (23). Only CMP-activated sialic acids can be recognized by the CMP-sialic acid transporter and undergo active transportation into the Golgi lumen where they serve as substrate for sialyltransferases (24,25). Rillahan and colleagues proposed that P-3F ax -Neu5Ac blocks sialylation globally via 2 mechanisms.…”
Section: Introductionmentioning
confidence: 99%
“…Initially, CMP-activated P-3F ax -Neu5Ac inhibits sialyltransferases directly and thereby prevents incorporation of natural sialic acids into assembling glycans. As a consequence, CMP sialic acids accumulate in the cell and disable UDP-N-acetylglucosamine 2-epimerase/ N-acetylmannosamine kinase (GNE/MNK), a key enzyme upstream in the de novo synthesis pathway of sialic acids (25,26). In a 2-step reaction, GNE/MNK catalyzes intracellular sialic acid precursors (UDP-N-Acetylglucosamine) to NAcetylmannosamine (ManNAc) and ManNAc-6-phosphate (ManNAc-6P) which is finally converted into CMP-Neu5Ac (27).…”
Section: Introductionmentioning
confidence: 99%
“…Since CMP is an inhibitor of sialyltransferases, its rapid removal from the Golgi complex is important to optimize sialyltransferase activity (33,34). The mammalian CST has been cloned by phenotypic correction of the Lec2 CHO cell CMPsialic acid transport mutant (31), and its identity has been further confirmed by functional expression in organisms that lack an endogenous CST, such as Saccharomyces cerevisiae and Escherichia coli (32,35).…”
mentioning
confidence: 99%